2021
DOI: 10.1115/1.4050806
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Friction Coefficient and Friction Vibration in Running-In Process Based on Cross Recurrence Plots

Abstract: Friction coefficient is difficult to measure in real application, whether it can be replaced by friction coefficient for dynamic analysis is an urgent issue to be solved. To study the correlation between the two signals, the friction tests were carried out under dry friction, starved and flooded lubrications, respectively. Cross recurrence plot (CRP) and its measures (recurrence rate, determinism, average diagonal line length and entropy) were used to explore the correlation. The results show that the more obv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…It is an important stage before it is put into normal operation. A tribological system is a nonlinear system affected by many factors [3][4][5]. The run-in state and its development directly affect the tribo-pair's work efficiency and serviceable life [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is an important stage before it is put into normal operation. A tribological system is a nonlinear system affected by many factors [3][4][5]. The run-in state and its development directly affect the tribo-pair's work efficiency and serviceable life [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ding et al [17] found that the friction noise attractor is chaotic, and the attractor evolution of friction noise can help identify the wear process. Zhou et al [18] studied the correlation between the aperiodic FIV and friction coefficient under different friction states by cross recurrence plot. Xu et al [19] characterized the surface wear state of a sliding-rolling contact through the features of the aperiodic FIV.…”
Section: Introductionmentioning
confidence: 99%